Jawaban Menteri Luar Negeri dalam rapat kerja dengan Komisi I, Dewan Perwakilan Rakyat RI tanggal 5 Pebruari 1990 (Departemen Luar Negeri, Republik Indonesia, 1990)
Responses of the Minister of Foreign Affairs to questions raised by member of the First Commission of the Parliament regarding the budget draft for 1990/1991.